Preliminary assessment of the association between DArT-SEQ SNP and some nutritional traits in African yam bean - Oluwole, O.O.; Olomitutu, O.E.; Paliwal, R.; Oyatomi, Olaniyi; Abberton, Michael T.; Obembe, O. (University of Benin, 2017)
African yam bean (AYB) is an underutilized tropical legume rich in protein and starch content. This study's aim was to use Diversity Arrays Technology (DArT) sequencing to study the ge-nome-wide association studies (GWAS) of nutritional traits. The study was carried out on 137 accessions in IITA, Ibadan. Seeds were harvested at maturity and analysed for protein, oil, and starch using Kjeltec, Soxtec, and Phenol-sulfuric acid assay method. Mixed Linear Model (MLM) was used for GWAS analysis by employing the TASSEL software. AYB protein content ranged from 17.13-27.15%, while the oil and starch content ranged from 0.74-2.27% and 60.58-69.84%, respectively. A total of 3.6K SNP was generated using a high-throughput DArTseq genotype-by-sequencing SNP approach in the AYB population. These generated SNPs were filtered for quality control, and the remaining useful 2.48K SNPs were used for the preliminary GWAS. We identified a promising source of genetic material for important grain nutritional traits that could be used in AYB breeding research. Identification of QTL/gene of protein, oil, and starch will contribute to our understanding of the genetic basis of natural variation in AYB grain nutritional traits.